(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The study examines the role of artificial intelligence (AI) is transforming the accounting profession in this dynamic world of business and accounting. The focus is on the challenges and opportunities for professional accountants in Bangladesh. The purpose is to understand how AI is reshaping skills, jobs, and ethics in this emerging economy like Bangladesh. The study used a qualitative research design. Data was collected through a single Focus Group Discussion (FGD). Seven experts participated. They represented accounting, IT, human resources, and corporate world. Thematic analysis revealed that AI drives efficiency but also causes acute job displacement fear of job loss among staff. This is a novel finding for the Bangladeshi context. Secondly, there is a prevalent skill and education gap in Bangladesh. This is a retraining crisis for senior professionals. The study suggests that the speed of automation is highly disruptive in emerging markets. Policy recommendations include mandatory AI literacy training, assessing current level of AI adoption and find out the ways to implement AI in major sectors to gain efficiency and effectiveness. To get maximum benefit from this a complete regulatory reforms is necessary.